Description of a new species of Gracixalus (Amphibia: Anura: Rhacophoridae) from Guangdong Province, southeastern China - Wang, Jian; Zeng, Zhao-Chi; Lyu, Zhi-Tong; Liu, Zu-Yao; Wang, Ying-Yong (Zootaxa, 2018)
A new species of tree frog, G. guangdongensis sp nov., is described based on a series of specimens collected from Dawuling Forest Station, Mount Nankun and Nanling Nature Reserve of Guangdong Province, southeastern China. The new species is distinguished from all known congeners by a significant genetic divergence at the mitochondrial 16S rRNA gene fragment examined (p-distance ≥ 4.6%) and the following combination of morphological characters: relatively small body size (SVL 26.1–34.7 mm in adult males, 34.9–35.4 mm in adult females); upper eyelid and dorsum lacking spines; supratympanic fold and tympanum distinct; dorsal and lateral surface rough, sparsely scattered with tubercles; ventral skin granular; tibiotarsal projection absent; toe-webbing moderately developed, finger webbing rudimentary; heels slightly overlapping when flexed hindlimbs are held at right angles to the body axis; brown to beige above, with an inverse Y-shaped dark brown marking extendeing from the interorbital region to the centre of the dorsum; males with a single subgular vocal sac and protruding nuptial pads with minute granules on the dorsal surface of the base of first finger. The discovery and description of Gracixalus guangdongensis sp. nov. represents the 14th species known in this genus.